Bictegravir/emtricitabine/tenofovir alafenamide ensures high rates of virological suppression maintenance despite previous resistance in PLWH who optimize treatment in clinical practice. (September 2022) - Armenia, Daniele; Forbici, Federica; Bertoli, Ada; Berno, Giulia; Malagnino, Vincenzo; Gagliardini, Roberta; Borghi, Vanni; Gennari, William; Cicalini, Stefania; Buonomini, Annarita; Teti, Elisabetta; Lanini, Simone; et al.
Highlights: In real-life settings, virological rebound after B/F/TAF switch is rare. Previous resistance alone does not affect B/F/TAF virological response. Previous INI-failures are associated with virological rebound under B/F/TAF. Previous resistance and INI-failures further increase the risk of B/F/TAF failure. ABSTRACT: Objectives: We evaluated virological response and resistance profiles in individuals who were virologically suppressed who switched to bictegravir/emtricitabine/tenofovir alafenamide (B/F/TAF) in real life. Methods: Survival analysis was used to assess probability of virological rebound (VR). Cumulative major resistance mutations (MRM) and cumulative genotypic susceptibility score (cGSS) were evaluated before the switch. Results: Overall, 283 individuals virologically suppressed for a median (interquartile [IQR]) time of 7 (3–9) y were analyzed. Of these, 20.8% were in first-line treatment, 13.1% were highly treatment-experienced (HTE), and 8.5% had experienced previous integrase inhibitor (INI)-failures. Before the switch, nucleotide reverse transcriptase inhibitor NRTI MRM prevalence was 29% (M184V:13.8%; any thymidine analogue mutation: 14.1%; K65R: 0.7%; K70E 0.4%); only three (2.1%) individuals showed INI major resistance mutations (Y143C/H/R [n = 1]; Y143C [n = 1]; N155H [n = 1]), and 82.0% of individuals received fully active B/F/TAF. Ninety-six wk after switch, the probability of VR was 5%, with only 12 events of VR at a median (IQR) viremia level of 284 (187–980) copies/mL, mainly transient. No significant associations between virological outcomes and genotypic susceptibility to B/F/TAF were observed. People who experienced previous INI failures showed a significantly higher adjusted hazard ratio (AHR [95% CI]) to experience VR under B/F/TAF (3.9 [1.1–13.4], P  = 0.031). This AHR increased in people who experienced INI failures and received partially active B/F/TAF (5.5 [1.4–21.1], P  = 0.013). Conclusion: Within 96 wk, a switch to B/F/TAF in individuals who were virologically suppressed ensured a very high rate of virological control in a clinical setting. Previous resistance alone did not affect B/F/TAF response. However, people who had previous INI failures were more prone to losing virological control under B/F/TAF.